2016
DOI: 10.5539/ijb.v8n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Up-Regulated Genes Response to Acute Hypo-Osmotic Stress in Hepatopancreas and Gill of the Pacific White Shrimps (Litopenaeus vannamei)

Abstract: Suppression subtractive hybridization (SSH) was applied to screen responsively up-regulation genes in hepatopancreas and gill of Litopenaeus vannamei induced by acute hypo-osmotic stress. In the hepatopancreas, 196 clones were randomly selected and sequenced. 131 non-redundant transcripts, corresponding to 41 genes, were found with elevated expressions. They were functionally clustered into eight biological processes which were protein synthesis and processing, carbohydrate metabolism and energy production, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Three different GST isoforms are connected in network 1 to another highly regulated protein, elongation factor 1‐delta (FC = 4.48, p = .0025). EF 1‐delta was found to be regulated in several studies of fish exposed to pollutants (Jeffries et al, 2015; Williams et al, 2003) and putative disease agents (Lü et al, 2014), as well as hypo‐osmotic stress in shrimp (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different GST isoforms are connected in network 1 to another highly regulated protein, elongation factor 1‐delta (FC = 4.48, p = .0025). EF 1‐delta was found to be regulated in several studies of fish exposed to pollutants (Jeffries et al, 2015; Williams et al, 2003) and putative disease agents (Lü et al, 2014), as well as hypo‐osmotic stress in shrimp (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Three different GST isoforms are connected in network 1 to another highly regulated protein, elongation factor 1-delta (FC = 4.48, p = .0025). EF 1-delta was found to be regulated in several studies of fish exposed to pollutants (Jeffries et al, 2015;Williams et al, 2003) and putative disease agents (Lü et al, 2014), as well as hypo-osmotic stress in shrimp (Liu et al, 2016 (Elarabany et al, 2017). Osmotic stress is known to induce erythrocyte cell death by opening Ca 2+ -permeable cation channels, increasing cytosolic Ca 2+ activity and triggering erythrocyte apoptosis (Lang et al, 2003).…”
Section: Regulation Of Antioxidant Functions During Salinity Stressmentioning
confidence: 99%
“…Three different GST isoforms are connected in network 1 to another highly regulated protein, elongation factor 1-delta (FC=4.48, p=.0025). EF 1-delta was found to be regulated in several studies of fish exposed to pollutants (Jeffries, Brander, Britton, Fangue, & Connon, 2015;Williams, Gensberg, Minchin, & Chipman, 2003) and putative disease agents (Lü et al, 2014), as well as hypo-osmotic stress in shrimp (Liu et al, 2016).…”
Section: Regulation Of Antioxidant Functions During Salinity Stressmentioning
confidence: 99%
“…The extraction of total RNA and reverse transcription, as well as the qRT-PCR, were performed per the methods of our previously paper (Wei et al, 2016 ). GDH -β, GS and TG were determined for each cDNA using qRT-PCR on a ROCHE Light Cycler 96 Real-Time Cycler PCR Detection System (Roche Applied Science, Mannheim, Germany) using the following specific primers, Forward/Reverse sequence for GDH -β (5'−3') (CTTTCCAGGATCGCATTTCT; AAGCAG CAGTACGGAGATCAA) and GS (GGCATGGAGCAGGAGTA; CGCCGCAGT AGTAGGGT); for TG (CCTCAGGATCTCCTTCACCA; TTGGGAAAACCTTCA TTTCG); as well as the β-actin (CGCGACCTCACAGACTACCT, GTGGTCATC TCCTGCTCGAA) (Li and Wormhoudt, 2015 ; Liu et al, 2016 ). The thermal cycling conditions for the qRT-PCR consisted of denaturation at 95°C for 15 min, followed by 40 cycles at 95°C for 15 s, 60°C for 30 s then a final hold at 60°C for 60 s (Wang et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a primary environmental factor, ammonia-N can rapidly increase mortality and lead to severe economic losses in shrimp cultivation industry (Cobo et al, 2014 ). Previous studies have also shown that various tissues of L. vannamei had been seriously affected when exposed to different ammonia stress levels (Racotta and Hernández-Herrera, 2000 ; Liang et al, 2016 ; Liu et al, 2016 ; Zhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%